2022
DOI: 10.3389/fnins.2022.940343
|View full text |Cite
|
Sign up to set email alerts
|

Potential mechanisms of acupuncture for neuropathic pain based on somatosensory system

Abstract: Neuropathic pain, caused by a lesion or disease of the somatosensory system, is common and distressing. In view of the high human and economic burden, more effective treatment strategies were urgently needed. Acupuncture has been increasingly used as an adjuvant or complementary therapy for neuropathic pain. Although the therapeutic effects of acupuncture have been demonstrated in various high-quality randomized controlled trials, there is significant heterogeneity in the underlying mechanisms. This review aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 177 publications
0
8
0
1
Order By: Relevance
“…In clinical practice, the common approaches to treating chronic pain include opioid analgesic medication [ 26 ], cognitive behavioral therapy [ 27 , 28 ], meditation, and acupuncture [ 29 , 30 ]. However, these approaches have various limitations.…”
Section: Clinical Evidence For Light Therapymentioning
confidence: 99%
“…In clinical practice, the common approaches to treating chronic pain include opioid analgesic medication [ 26 ], cognitive behavioral therapy [ 27 , 28 ], meditation, and acupuncture [ 29 , 30 ]. However, these approaches have various limitations.…”
Section: Clinical Evidence For Light Therapymentioning
confidence: 99%
“…Acupuncture may inhibit neuronal activity caused by neuropathic pain by reducing pain-related ion channel and protein kinase activation. In addition, EA reduced the release of inflammatory factors such as tumor necrosis factor α and interleukin-1β, suppressing the neuronal excitability and inflammatory response [71] . Acupuncture as a non-pharmacological treatment has the potential to activate the descending pain control system by increasing the levels of spinal or brain 5-hydroxytryptamine, and opioid peptides [110] .…”
Section: Discussionmentioning
confidence: 99%
“…Possible mechanisms for the regulation of sympathetic nerves by acupuncture to relieve neuropathic pain Acupuncture as an alternative therapy has been widely used for the treatment of neuropathic pain such as peripheral neuropathic pain, prosopalgia, and postherpetic neuralgia [70][71][72] . Acupuncture has a benign effect on the ANS regulating function [20,[73][74] .…”
Section: The Inflammatory Effects Of Sympathetic Innervationmentioning
confidence: 99%
“…96 Acupuncture, as a early form and foundation of peripheral stimulation, 97,98 provide an alternative or adjunctive therapy for neuropathic pain via increasing the level of spinal or brain 5-hydroxytryptamine (5-HT), norepinephrine (NE), and opioid peptides. 99 Acupuncture are beneficial and cost-effective approaches for easing peripheral neuropathic pain and hence can be considered for peripheral neuropathic pain management. 100 A study showed that acupuncture resulted in significant improvement in CIPN symptoms compared with usual care.…”
Section: Peripheral Neuropathic Pain Syndromementioning
confidence: 99%